KINERJA APARATUR SIPIL NEGARA PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KABUPATEN PARIGI MOUTONG - Sarman, Sarman (Katalogis, 2018)
This study aims to examine and analyze and to determine the performance of the State Civil Apparatus at the Human Resources Development and Human Resources Agency in Parigi Moutong District. This study uses Performance theory proposed by Robbins, (2001: 187), which includes aspects of Motivation, Ability, and Opportunity. This research uses research informants totaling 5 (five) people, the determination of informants is done using purposive sampling technique. The types of data used in this study include secondary data and primary data. Data collection techniques used are observation, interviews and documentation. Data analysis carried out is an interactive model which includes Data Collection, Data Reduction, Data Presentation and Interesting Conclusions. The results of the study can be concluded that the performance of the State Civil Apparatus in the Personnel and Human Resource Development Agency of Parigi Moutong District has not been as optimal as expected. It is seen in the aspect of Motivation, it is quite good that the motivation obtained by employees whether through the leadership or from among employees motivates each other. Aspects of ability, employees are not good at understanding the task so that they are unable to work optimally. And on the aspect of opportunity, employees have not evenly been given the flexibility to plan and carry out their duties and obligations and are given the opportunity to be able to participate in each activity and take part in training and education in the form of additional capacity and experience.